Rwanda and the question of Commonwealth relevance. Issue 3 (3rd July 2019) - Johnstone, Lyn
ABSTRACT: Rwanda's accession to the Commonwealth is often cited as a reason for the organisation's continued relevance. And yet, in spite of this positioning as poster child for a more cosmopolitan Commonwealth, there is very little evidence, in the corpus of Commonwealth literature, to show how accession of states such as Rwanda boost the argument for relevance. In 2015, I travelled to Rwanda to gain an understanding of the effect that Commonwealth membership has had on the country and vice versa. Using this evidence, I draw conclusions about the effect that Rwanda and the Commonwealth have had on each other.